Trans‐oral robotic surgery: a safe and effective tool in head and neck surgery in an Australian rural setting. Issue 11 (12th April 2021) - Huang, Johnson; Phillips, Nicholas; Nightingale, James; Kondalsamy‐Chennakesavan, Srinivas; Grigg, Roger; Mahendran, Suresh
Abstract: Background: Trans‐oral robotic surgery (TORS) facilitates surgical resection of tumours as an alternative to open surgery and has demonstrated favourable oncological results. Given the novelty of TORS and the paucity of evidence on TORS‐specific complications in a rural setting, we report our experience with TORS at an Australian rural head and neck centre. Methods: A retrospective review of all robotic cases performed at a regional head and neck centre in Queensland was undertaken from 2014 to 2019. Patient demographics, pre‐operative surgical risk, complications and outcomes such as margins and cancer recurrence were recorded. Complications were graded based on the Clavien‐Dindo grading system. Descriptive statistics were used to present patient characteristics and statistical analyses were performed using Stata. Results: Forty‐two TORS surgeries were performed. Twenty‐one had histology confirming malignancy. There were no adverse intraoperative effects. Overall, seven patients (16.7%) had at least one complication. Four were recorded as a Clavien‐Dindo 3b (post‐operative bleed, wound infection and drain dislodgment). Of two cases with residual positive margins, one declined further surgery, and another received chemoradiotherapy. One patient recurred with distant metastatic disease, and another had locoregional nodal recurrence. The distribution of complications was significant across the pre‐operative risk categories for both American Society of Anaesthesiologists and surgical risk score ( P  = 0.02). Conclusion: TORS in a rural head and neck centre is a safe and viable treatment option for patients so long as this is undertaken with appropriate training, mentorship and teamwork. Abstract : Trans‐oral robotic surgery (TORS) facilitates surgical resection of tumours as an alternative to open surgery and has demonstrated favourable oncological results. Given the novelty of TORS, the paucity of evidence on TORS‐specific complications in a rural setting, we report our experience with TORS at an Australian rural head and neck centre.